G358(P) Are we recognising an elevated BMI at our general paediatric clinics? it's time to intervene…. (27th April 2016) - Foley, D; Gallagher, P
Abstract : Aim: The aim was to assess the frequency with which healthcare professionals acknowledged children attending general paediatric clinics were overweight or obese. We then analysed what interventions, investigations and referrals these children received in relation to weight management. The data has been used to create a best practice guideline and improve local awareness. Methods: Data was retrospectively collected from a random cohort of n = 172 patients attending general clinics during September and October 2015. Patients were aged between 2 to 15 years. Notes were analysed from the two most recent OPD visits and GP letter. Patient data collected included; height, weight, BMI, co-morbidities and purpose of OPD visit. We assessed if overweight or obese children had been correctly identified with a BMI >85th centile, and, if so what intervention they received. Overweight and obesity in children was defined as a Body Mass Index (BMI) centile for age, of >85th and >95th centile respectively. 1 Results: Of 78 girls and 94 boys (n = 172), 12.2% (n = 21) were overweight 2 and 20.9% (n = 36) were obese. 2 In 48 of the 57 (84.2%) overweight or obese children identified, the BMI was not calculated. Of n = 36 obese patients, 5 were educated on weight management strategies and referred to the dietician and 1 received further medical investigations. Weight issues were specifically discussed in 2 obese patients but no further intervention made. 35 asthmatics were identified within the cohort and 34.3% (n = 12) were overweight or obese. Conclusion: This audit highlighted a failure in the current system to identify, manage and provide appropriate intervention for overweight and obese children compared to international best practice. The levels of overweight and obese patients compared similarly to international published data. As a consequence of these findings we have implemented the following measures: Mandatory BMI calculation and centile for all patients on their initial assessment. Creation of a local guideline with clear cut-off values for; dietician and weight loss program referral, further defined medical investigations and tertiary endocrine referral. Patient information booklet to educate children and families.